Pengaruh Penerapan E-Filing, Sosialisasi Perpajakan, Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Agustini, Komang Dewi; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p19, 2019)
This research aims to finding the effect of implementing e-filling, taxes’ socialization, and taxation sanctions in the level of personal taxpayers’ compliance in KPP Pratama Denpasar Barat. The sample of this research was 100 respondents by applying accidental sampling, while the data collection was obtained by questionnaire. The data analysis was done by double linear regression anaylisis. The findings showed that implementing e-filling, taxes’ socialization, and taxation sanctions deliver positive influnces towards personal taxpayers’ compliance. Keywords : Taxpayers’ compliance, e-filling, socialization, sanctions